Voltage Profile Improvement of Low Voltage Distribution System using D-STATCOM (International Journal of Current Engineering and Technology, 2015)
This paper presents the design of a distribution static compensator (D-STATCOM) for voltage sag mitigation in an 11kV/440V Low Voltage Radial Distribution system in different loading conditions. The model is based on the voltage source converter (VSC) principle. A new PWM based control scheme has been implemented to control the electronic valves in VSC. The D-STATCOM injects current into the system to mitigate the voltage sags. In the present work the 6-pulse D-STATCOM configuration with IGBT has been designed using Matlab/Simulink. Accordingly, simulations are carried out to illustrate the use of D-STATCOM in mitigating voltage sag in the low voltage distribution system. Simulation results prove that the D-STATCOM is capable of mitigating voltage sag as well as reducing the power loss in the distribution system. Cost calculation has been made before and after installation of D-STATCOM.
Keywords: Low Voltage Distribution system; voltage sag; D-STATCOM; cost calculation